Text-to-Image Generative Αrtificial Intelligence As Conceptual Mechanism For Architectural Design - Socrates Yiannoudes (Universitas Atma Jaya Yogyakarta, 2025)
This study investigates the potential of text-to-image generative AI applications to be used as exploration mechanisms for architectural design rather than mere visualisation tools. We examine whether text-to-image generative AI applications can